PENGARUH BRAND REPUTATION DAN PERCEIVED RISK TERHADAP PURCHASE INTENTION MELALUI BRAND TRUST PADA PENGGUNA APLIKASI CAROUSELL GENERASI Z - Tasya Sholehah; Dita Puruwita; Kusworo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the influence of brand reputation and perceived risk on purchase intention through brand trust as a mediating variable among Generation Z users of the Carousell application. The study was conducted in response to the rapid growth of the preloved marketplace, highlighting the importance of understanding the factors influencing consumers’ purchase intentions. A quantitative approach was employed by distributing online questionnaires via Google Forms to 150 respondents selected using a purposive sampling technique. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The results indicate that brand reputation has a positive and significant effect on brand trust, while perceived risk has a negative and significant effect on brand trust. In addition, brand trust has a positive and significant effect on purchase intention. The findings also reveal that brand reputation positively and significantly influences purchase intention, whereas perceived risk negatively and significantly influences purchase intention. Furthermore, brand trust is proven to mediate the relationship between brand reputation and perceived risk toward purchase intention. These findings suggest that improving brand reputation, strengthening transaction security, and enhancing user data protection are essential to building consumer trust and increasing purchase intention on marketplace platforms.